Detections of the Gravitational Waves - Bassalo, José Maria Filardo; Cattani, M. (Caderno Brasileiro de Ensino de Física, 2016)
On February 11, 2016, during a conference held at the National Science Foundation (NSF), in Washington, D.C., the American physicist David Reitze, Executive Director of the Laser Interferometer Gravitacional-Wave Observatory (LIGO) announced that it had been observed on September 14, 2015 Gravitational Waves (GW). This event was named GW150914. A second observation was also done by the LIGO on December 26, 2015 named GW151226. The signals of these two events are similar and are due to the coalescence of a binary black holes (BH). The GW sources are distant, respectively, of ~ 410 Mpc and ~ 440 Mpc from the Earth. To understand the significance of this extraordinary events we will make a historical summary of the GW and the BH.